Running economy: neuromuscular and joint-stiffness contributions in trained runners - Tam, N.; Tucker, R.; Santos-Concejero, J.; Prins, D.; Lamberts, R. P. (International Journal of Sports Physiology and Performance, 2019)
Context: It is debated whether running biomechanics make good predictors of running economy, with little known about the neuromuscular and joint-stiffness contributions to economical running gait. Purpose: To understand the relationship between certain neuromuscular and spatiotemporal biomechanical factors associated with running economy. Methods: Thirty trained runners performed a 6-min constant-speed running set at 3.3 m·s-1, where oxygen consumption was assessed. Overground running trials were also performed at 3.3 m·s-1 to assess kinematics, kinetics, and muscle activity. Spatiotemporal gait variables, joint stiffness, preactivation, and stance-phase muscle activity (gluteus medius, rectus femoris, biceps femoris, peroneus longus, tibialis anterior, and gastrocnemius lateralis and medius) were variables of specific interest and thus determined. In addition, preactivation and ground contact of agonist-antagonist coactivation were calculated. Results: More economical runners presented with short ground-contact times (r = .639, P < .001) and greater stride frequencies (r = -.630, P < .001). Lower ankle and greater knee stiffness were associated with lower oxygen consumption (r = .527, P = .007 and r = .384, P = .043, respectively). Only lateral gastrocnemius-tibialis anterior coactivation during stance was associated with lower oxygen cost of transport (r = .672, P < .0001). Conclusions: Greater muscle preactivation and biarticular muscle activity during stance were associated with more economical runners. Consequently, trained runners who exhibit greater neuromuscular activation prior to and during ground contact, in turn optimizing spatiotemporal variables and joint stiffness, will be the most economical runners.